1992
DOI: 10.1159/000163699
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Defining Shared Human Macrophage-Endothelial Antigens

Abstract: We have selected several monoclonal antibodies (mAbs) produced using human rheumatoid arthritis (RA) synovial macrophages (mφs) as immunogen. Of these, mAbs 8H2, 10G7 and 10G9 showed cross reactivity with endothelium, suggesting common antigens between these cell types. We have determined the spectrum of reactivity of these mAbs on hematopoietic cell lines, peripheral blood cells, and inflammatory and non-inflammatory tissues by immunohistochemistry. MAb 8H2 does not react with the myeloid cell lines HL60 (mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Immunoperoxidase staining. Fresh synovial tissues were frozen and 4‐μm sections were cut and immunoperoxidase stained using an avidin–biotin technique (Vector Laboratories, Burlingame, CA) (29–32). Slides, air dried for 2–16 hours, were fixed in cold acetone for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoperoxidase staining. Fresh synovial tissues were frozen and 4‐μm sections were cut and immunoperoxidase stained using an avidin–biotin technique (Vector Laboratories, Burlingame, CA) (29–32). Slides, air dried for 2–16 hours, were fixed in cold acetone for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, expression of CD13 has been reported to be increased in the synovial fluid of patients with rheumatoid arthritis, a process that involves the infiltration of inflammatory cells into the affected region [42][43][44][45][46]. A second report found that synovial CD13 levels correlated positively with the number of infiltrating lymphocytes of arthritis patients [47].…”
Section: Cd13 Is Not Required For Certain Acute Inflammatory Processesmentioning
confidence: 96%